PENTINGNYA UJI ASUMSI KLASIK PADA ANALISIS REGRESI LINIER BERGANDA (STUDI KASUS PENYUSUNAN PERSAMAAN ALLOMETRIK KENARI MUDA [CANARIUM INDICUM L.]) - Mardiatmoko, Gun (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Generally, in the preparation of multiple linear regression or allometric equations, the T and F tests were carried out directly, while various tests are not performed. Therefore, this study aims to provide examples of establishing a good and complete regression equation by presenting a case study of preparing young canary allometric equations. Furthermore, Canary (Canarium Indicum L) was selected because it provides environmental services, especially in handling climate change, which has not been much studied. This article also attempts to establish the allometric equations of young canaries to be used in dealing with climate change. The results obtained by the allometric equation Y = -941,765 + 399,903 X1 + 3,429 X2, showed that it was good because it has undergone several tests, but cannot be operationalized due to the low determinant value of RSquare: 0.318. In order for allometric equations to work and function properly, it is necessary to perform various tests first and once the regression equation is obtained, it should be supported by a high RSquare value